Director | Director of Photography | Colorist | VFX

Un=T+nT

nT= I+T+X

Un=T+(I+T+X)

I : Being

T : Thought

X : Strictly different than 0 & T (can be written : I+T < I+T+X ) where T « can » be equal to 0

An important key is the reflection between the forumla Un=T+nT and I=I where the latest lacked the idea of an additional equal term different than 0 for the latest.

We could write it like this :

Un=I+T

Un=T+(I+T+X)

I+T=T+(I+T+X)

if T=0

Un=I

so

I=I+X

X is a thought (T) but unlike T it can never be equal to 0

X≥ T only if X≠ 0

Which leads us to X > T if T=0 OR X≥ T if T>0

Its only condition is to have a prior term « T » even if this one is equal to 0.

X will be the « n » Terms following T that is strictly greater than 0.

Void or « I » is an impossibility because another term will always follows it even if this term is the void.

T has no conditions but by its very definition, allows the set of the term I plus something even if something is empty.

With this rule we can create a two, I+T where one is equal to 0 and the other imply that it is equal to 0 only if it’s equal to I (Un=I)